New records of two families, four genera and eight species of spiders (Arachnida: Araneae) in Iraq across latitudinal gradients - SHUROOQ ABDULLAH NAJIM; SADEQ MITHAL AL-ESA (Society for Indonesian Biodiversity, 2025)
Abstract. Najim SA, Al-Esa SM. 2025. New records of two families, four genera and eight species of spiders (Arachnida: Araneae) in Iraq across latitudinal gradients. Biodiversitas 26: 4167-4179. Spiders (Order: Araneae) are among the most diverse and ecologically important predators worldwide, playing a critical role in maintaining ecological balance across terrestrial ecosystems. Despite Iraq's diverse landscapes, which range from arid deserts to lush mountainous regions, its spider fauna remains significantly understudied. In light of this knowledge gap, this study presents new faunistic records of spiders from three major regions of Iraq: Basrah, Baghdad, and Sulaymaniyah, spanning different latitudinal zones. Fieldwork was conducted between January 2023 and December 2024, during which specimens were collected using standard arachnological methods, including hand sampling and pitfall trapping. Specimens were identified using reliable taxonomic keys, with detailed examination of morphological features such as habitus, epigynum (female genitalia), and pedipalps (male reproductive structures). These features were photographed using high-resolution macro imaging for accurate documentation and comparison. The study records eight spider species newly reported from Iraq, representing two new families, four new genera and eight species, broadening the known arachnid diversity of the country. The newly recorded species include: Megalepthyphantes nebulosus,1?, Family: Linyphiidae; Mimetus laevigatus,2?, Family: Mimetidae; Marilynia bicolor,2?, Family: Dictynidae; Philodromus longipalpis,5?, Family: Philodromidae; Argiope bruennichi,1?, Neoscona subfusca,1?,1?, Family: Araneidae; Steatoda erigoniformis,4?,5?, Family: Theridiidae; Bassaniodes caperatus,1?, Family: Thomisidae. All collected specimens have been preserved and deposited in the Natural History Museum of Basrah University, Iraq. These findings not only contribute to the regional biodiversity records but also emphasize the need for continued arachnological surveys across Iraq's varied habitats to better understand species distribution and ecological interactions.